Perbanyakan Tunas Mikro pada Beberapa Umur Simpan Umbi dan Pembentukan Umbi Mikro Bawang Merah pada Dua Suhu Ruang Kultur - Diny Dinarti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
Shallot bulb generally stored for several month before planted in the fi eld. Since explant age is one of important factors in tissue culture development, storage period of shallot bulb might alter the explant growth in vitro. Shoots of shallot formed in the in vitro culture should form bulbs before can be use as seedling, and temperature may affect micro bulb induction. Two experiments had been conducted to evaluate 1) the effect of storage period in the fi eld on the growth of shallot explant in vitro and 2) the effect of culture room temperature in microbulbs induction of shallot. In the fi rst experiment, shallot bulb had been stored for 1, 2, 3 and 4 months before used as explants. Storage period signifi cantly infl uenced the explant growth in vitro. Bulb with 2 months storage gave the best performance on number of micro shoot, number of leaves and roots, and less of vitrifi cation. Micro shoots on three weeks after planting (WAP) was feasible to use as propagule for shallot micro bulb induction. In the second experiment, shoots from propagation medium was transplanted to bulb induction medium and grown in growth chamber with different temperatures (day/night) 20/17 oC and 30/27 oC, respectively. Micro bulb induction was infl uenced by temperature. Lower temperature showed good results for number of leaves, length of leaves, number of roots, and length of roots. However, temperature of 30/27 oC gave the best result on number of micro bulb, diameter of bulb and bulb width:bulb disk diameter ratio. Keywords: Allium, explants age, micro bulb, temperature, 2ip